2020
DOI: 10.4081/aiua.2020.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms and antibiotic susceptibilities isolated from urine cultures

Abstract: Objectives: Urinary tract infection (UTI) is the second most common cause of infection among all infectious diseases at hospitals. Antibiogram results are needed to maintain treatment in patients with suspected UTI. However, empirical antibiotic treatment is initiated in patients since it takes time to obtain the results of antibiograms. The aim of this study was to evaluate the urine culture and antibiogram results of patients who were admitted to our hospital with suspected UTI and compare the results with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The current study included 180 urine samples from UTI patients, out of which growth of organisms was observed in a total of 93 samples. The most significant growth was of the organism E. coli, found in 30 samples (32.25%), followed by Candida albicans in 17 samples ( [13]. In the present study, the incidence of E. coli was 51.66%, which was quite similar to the findings reported by Hamza et al, but lower than the incidence reported by Gul and Gurbuz, who found E. coli in 68.4% of 1211 urine samples [12,13].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study included 180 urine samples from UTI patients, out of which growth of organisms was observed in a total of 93 samples. The most significant growth was of the organism E. coli, found in 30 samples (32.25%), followed by Candida albicans in 17 samples ( [13]. In the present study, the incidence of E. coli was 51.66%, which was quite similar to the findings reported by Hamza et al, but lower than the incidence reported by Gul and Gurbuz, who found E. coli in 68.4% of 1211 urine samples [12,13].…”
Section: Discussionsupporting
confidence: 88%
“…Another study conducted by Gul and Gurbuz involved 1211 urine samples, in which the organisms isolated were 0.17% Acinetobacter , 0.58% of Acinetobacter baumannii , 0.08% of Alcaligenes faecalis , 0.08% of Burkholderia cepacia , 1.24% of Candida albicans , 0.08% of Candida famata , 0.17% of Candida kefyr , 0.08% of Candida krusei , 0.25% of Candida spherica , 0.25% of Candida tropicalis , 0.17% of Citrobacter freundii , 0.25% of Citrobacter koseri , 0.08% of Enterobacter aerogenes , 0.74% of Enterobacter cloacae , 0.33% of Enterococcus species, 4.5% of Enterococcus faecalis , 0.74% of Enterococcus faecium , 68.4% of Escherichia coli , 2.8% of Klebsiella species, 0.5% of Klebsiella oxytoca , 7.2% of Klebsiella pneumoniae , 0.25% of Morganella morganii , 0.33% of Proteus species, 1.73% of Proteus mirabilis , 0.33% of Providencia rettgeri , 1.2% of Pseudomonas aeruginosa 10.08% of Salmonella species, 0.17% of Serratia fonticola , 0.17% of Serratia liquefaciens , 0.08% of Serratia marcescens , 0.08% of Shigella sonnei , 0.33% of Staphylococcus aureus , 1.9% of Staphylococcus epidermidis , 0.25% of Staphylococcus haemolyticus , 0.08% of Staphylococcus hominis , 0.5% of Staphylococcus saprophyticus , 0.08% of Staphylococcus warneri , 0.17% of Streptococcus species, 15% of Streptococcus agalactiae , 0.08% of Streptococcus constellatus , 0.17% of Streptococcus dysgalactiae , 0.25% of Streptococcus mitis , 0.08% of Streptococcus salivarius , and 0.08% of Streptococcus sanguinis [ 13 ]. In the present study, the incidence of E. coli was 51.66%, which was quite similar to the findings reported by Hamza et al, but lower than the incidence reported by Gul and Gurbuz, who found E. coli in 68.4% of 1211 urine samples [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar high resistance rates, especially for E. coli , have been reported by other studies in our country. [14,20,26] These results emphasize the importance of antibiotic stewardship programs. Since the national surveillance and infection control programs started in Turkey in 2005, health care-associated infection rates have declined over the past 10 years.…”
Section: Discussionmentioning
confidence: 84%
“…Recent research from Romania shows 12.6% cefuroxime resistance in urine isolates of E. coli (12). Other neighboring countries report 36% resistance in 2018 (13).…”
Section: Discussionmentioning
confidence: 99%